Ten-year trends of delayed sequential bilateral cataract surgery (DSBCS) in Sweden : a register-based study - Viberg, Andreas; Bro, Tomas; Behndig, Anders; Kugelberg, Maria; Zetterberg, Madeleine; Nilsson, Ingela; Lundström, Mats (Eye and Vision, 2024)
Purpose: To study the trend of delayed sequential bilateral cataract surgery (DSBCS) in Sweden in the past decade. Methods: This register-based cohort study utilized data from the Swedish National Cataract Register (NCR) from 2010 through 2019. Register files from patients who underwent cataract surgery in both eyes during the study period were linked using their social security numbers. Bilateral surgeries on different days were classified as DSBCS. The study investigated the association between DSBCS within 3 months and several variables with stratification and multivariate logistic regression. The following variables were used: operation year, region, private or public unit, age, sex, indication for surgery, type of intraocular lens (IOL), preoperative visual acuity, ocular comorbidity, posterior capsule rupture and perioperative difficulties. Results: During the study period, 368,106 patients underwent DSBCS, of which 62.6% (n = 230,331) had bilateral surgery within 3 months. The median time between the surgeries was 61 days (interquartile range 26–161 days), showing regional variations. Better visual acuity in the fellow eye, presence of ocular comorbidity, various perioperative events and complications were associated with longer time to surgery of the second eye. Conversely, cataract surgery in more recent years, private clinic, increasing age, anisometropia and multifocal IOL were associated with shorter timespan between surgeries. Conclusions: The majority of DSBCS were conducted within a 3-month timeframe, with the interval between surgeries decreasing throughout the study period. Several rational factors were associated with the time difference, in addition to regional variations. Many patients would probably benefit from less time between the surgeries, and we encourage a clinical practice taking the whole patient’s visual function into account.
Keywords: Cataract; Cataract surgery; Delayed sequential bilateral cataract surgery; Register-based study